2018
DOI: 10.1002/mnfr.201700844
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Inhibits Colorectal Cancer Cell Migration by Downregulating Bmi‐1 Through Enhanced miR‐200c Expression

Abstract: NaB inhibits CRC cell migration by enhancing miR-200c expression-mediated downregulation of Bmi-1. These findings support the utility of NaB in colorectal cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…The key roles of Bmi‐1 in cell migration, autophagy, ATP production, and ROS generation have been reported in several studies . Thus, we expected that NaB would modulate migration, autophagy, ATP production, and ROS generation through the miR‐139‐5p/Bmi‐1 axis in human bladder cancer cells.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…The key roles of Bmi‐1 in cell migration, autophagy, ATP production, and ROS generation have been reported in several studies . Thus, we expected that NaB would modulate migration, autophagy, ATP production, and ROS generation through the miR‐139‐5p/Bmi‐1 axis in human bladder cancer cells.…”
Section: Resultsmentioning
confidence: 83%
“…Accumulating evidence has proven that Bmi-1 is a key target in the clinical treatment of various malignancies due to its modulated roles in AMPK-dependent autophagy and cell migration. 18,[20][21][22] The miR-200 family is closely related to the EMT, and upregulating the miR-200 family leads to a reversal of the EMT by regulating Bmi-1. 20,46,58 Moreover, another original study demonstrated that cells derived from Bmi1 -/mice have impaired mitochondrial function, which led to a marked increase in the intracellular levels of ROS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations